Statistical Analysis of the Sensitivity of CRS-R Scale Projects in Consciousness Evaluation - Yonghong ZHANG; Xiaolin ZENG; Wei SHEN; Zhencheng CHEN; Linghui HE; Xinfei ZHANG (康复学报)
Objective:To observe the differences in the importance of the items in the conscious state assessment of the Coma Recovery Scale-Revised (CRS-R).Methods:A total of 480 patients with disturbance of consciousness were assessed by Chinese version of CRS-R. The data were introduced into SPSS 17.0 statistical software, and the correlation between each project and the state of consciousness was analyzed by using the correlation analysis function and decision tree function. It was analyzed whether the difference of this correlation was statistically significant.Results:The correlation between exercise, hearing, visual and consciousness status was the highest; the difference between exercise and other items was statistically significant (P<0.05), auditory, visual and other items (P<0.05), but the difference between auditory and visual acuity was not statistically significant (P>0.05).Conclusion:The CRS-R are different in the importance of the state of mind assessment, and the exercise, hearing and visual needs are more important than other items.